Pedagogical Processes in Learning English Language at Secondary School Level in Sikkim, India - Roshni Sharma; Sudarshan Mishra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
English has a significant role in every state in the school curriculum, and several scholars have researched the status of teaching English at secondary level. The purpose of teaching English is to build multilingual languages that can enrich our entire language; this has been an ongoing national vision. The weak status of teaching English and the use of conventional teaching methods are found in the study of literature. It is ironic, however, that while English enjoys a high status in the wake of globalization, it is quite inadequate and unproductive to teach and learn in educational institutions. Present strategies of teaching English in the classroom are no longer viable, but they can be 'communicatively' driven.The key disadvantages are the low status of teaching English, non-availability of professionally trained and educated teachers, less weighting provided for teaching English and no proper transactional strategies adopted for teaching. In this sense, the extent of the pedagogical processes of learning the English language must be examined. The target population of the current study in the South district of Sikkim was limited to 90 teachers teaching English in 30 secondary schools. Classroom observation schedule covering the aspects like engage, explore, explain, elaborate, evaluate was used for collection of data.Classroom observation is also one of the powerful methods of monitoring the success of the instructor in the classroom. Through this study, attempt has been made to see the extent as to how constructivist approach is used by the teachers in the teaching learning processes. Conversely, study has explored the teaching processes used by English teachers in the classroom towards learning English language at secondary schools in Sikkim. The sequential processes are mainly used to link up the connection between past and the present learning experience, designising activities for students engagement, assess learning outcomes, type of resource used in learning, identifying  and developing concepts, reconstructing students knowledge, assessing students  current level of  understanding in listening, speaking, reading and writing, elaboration through recapitulative questions, development of higher order thinking, evaluation of students of key concepts and skills, identifying and motivating the students to identify future learning goals and evaluating students knowledge through quiz, debate, role play, recitation, tests, observation and performance dialogue, essay and summary writing and projects, respectively.